Application of a drainage film reduces fibroblast ingrowth into large‐pored polyurethane foam during negative‐pressure wound therapy in an in vitro model. Issue 5 (12th August 2013) - Wiegand, Cornelia; Springer, Steffen; Abel, Martin; Wesarg, Falko; Ruth, Peter; Hipler, Uta‐Christina
Abstract Negative‐pressure wound therapy (NPWT) is an advantageous treatment option in wound management to promote healing and reduce the risk of complications. NPWT is mainly carried out using open‐cell polyurethane (PU) foams that stimulate granulation tissue formation. However, growth of wound bed tissue into foam material, leading to disruption of newly formed tissue upon dressing removal, has been observed. Consequently, it would be of clinical interest to preserve the positive effects of open‐cell PU foams while avoiding cellular ingrowth. The study presented analyzed effects of NPWT using large‐pored PU foam, fine‐pored PU foam, and the combination of large‐pored foam with drainage film on human dermal fibroblasts grown in a collagen matrix. The results showed no difference between the dressings in stimulating cellular migration during NPWT. However, when NPWT was applied using a large‐pored PU foam, the fibroblasts continued to migrate into the dressing. This led to significant breaches in the cell layers upon removal of the samples after vacuum treatment. In contrast, cell migration stopped at the collagen matrix edge when fine‐pored PU foam was used, as well as with the combination of PU foam and drainage film. In conclusion, placing a drainage film between collagen matrix and the large‐pored PU foam dressing reduced the ingrowth of cells into the foam significantly. Moreover, positive effects on cellular migration were not affected, and the effect of the foam on tissue surface roughness in vitro was also reduced.